Heavy metals Cd and Cr found in sponges (porifera) at spermonde archipelago Zone II. Issue 1 (March 2020) - Melawaty, L; Tahir, A; Djonny, M
Abstract: Samalona and Barrang Lompo Islands are located in zone II of Spermonde Archipelago with the nearest distance is about 5 km from Makassar city beach. The close distance causes heavy metals as pollutants produced from activities in Makassar city and it surroundings to be carried out to zone II of Spermonde Archipelago waters. Marine biotas used as a bioindicator of heavy metals (Cd and Cr) pollution were sponges (Porifera). Analysis results by ICP-OES indicated that the largest quantities of the heavy metals (Cd and Cr) were found in sponge Xestospongia, i.e 1.250 mg/kg and 5.400 mg/kg dry weight, respectively.